Differential self-report error by socioeconomic status in hypertension and hypercholesterolemia: INSEF 2015 study - Kislaya, Irina (2019)
Background: This study aimed to compare self-reported and examination-based prevalence of hypertension and hypercholesterolemia in Portugal in 2015 and to identify factors associated with the measurement error in self-reports. Methods: We used data from the Portuguese National Health Examination Survey (n = 4911), that combines personal interview, blood collection and, physical examination. Sensitivity and specificity of self-reported hypertension and hypercholesterolemia were calculated. Poisson regression was used to estimate prevalence ratios (PRs) of underreport of hypertension and hypercholesterolemia according to sex, age, socioeconomic status (education and income) and general practitioner (GP) consultation in the past year. Results: Sensitivity of self-reports was 69.8% for hypertension and 38.2% for hypercholesterolemia. Underreport of hypertension was associated with male gender (PR = 1.54), lack of GP consultation (PR = 1.70) and being 25–44 years old (PR = 2.45) or 45–54 years old (PR = 2.37). Underreport of hypercholesterolemia was associated with lack of GP consultation (PR = 1.15), younger age (PR = 1.83 for 25–44 age group and PR = 1.52 for 45–54 age group), secondary (PR = 1.30) and higher (PR = 1.27) education. Conclusion: Self-reported data underestimate prevalence of hypertension and hypercholesterolemia. Magnitude of measurement error in self-reports varies by health conditions and population characteristics. Adding objective measurements to self-reported questionnaires improve data accuracy allowing better understanding of socioeconomic inequalities in health.